TECHNICAL AND IMPLEMENTATIONAL ISSUES OF USING A VIDEO PLATFORM (FLIP.COM) FOR ONLINE LEARNING FOR TEACHERS IN KENINGAU, SABAH - Mohd. Zaki Ishak; Wirawati Ngui; Tan Choon Keong; Crispina Gregory K Han; Haridah Utu Satu (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The recent Covid-19 health pandemic (2020 – 2022) had caused great concern for educators across the globe. Schools were closed under the Moverment Control Act of each respective country to curb the spread of the virus. School lessons were replaced with online sessions. Purpose: The main purpose of this research is to explore and share teachers’ experience and perceptions for using an online video platform (flip.com) for teaching and learning. Teachers related these experiences via research workshops conducted at the 4 venues in Sabah. Methods: Data were elicited via the reflection notes approach and analyzed qualitatively to support the investigation. The researchers reported findings from selected a sample of 12 informants from the Kota Kinabalu Workshop, Sabah. Results: Eight out of twelve informants registered positive perceptions regarding the usage and suitability of flip.com for non-Mathematic subjects while negative comments were for the unsuitability usage for Mathematic, requests for professional development training and some technical issues while implementing the software. Recommendation: The research recommended that in order for an innovation such as flip.com to be accepted teachnologically by fulfilling the perceived usefulness and perceived ease-to-use components of the TAM Model, teachers’ comments on the feature of usefulness, user-friendliness of the interfaces and technicality issues of the software must be considered closely by the software provider.